2019
DOI: 10.5194/tc-2019-79
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring mechanisms responsible for tidal modulation in flow of the Filchner-Ronne Ice Shelf

Abstract: An extensive network of GPS sites on the Filchner-Ronne Ice Shelf and adjoining ice streams show strong tidal modulation of horizontal ice flow at a range of frequencies. A particularly strong (horizontal) response is found at the fortnightly (M sf ) frequency. Since this tidal constituent is absent in the (vertical) tidal forcing, this observation implies the action of some nonlinear mechanism. Another striking aspect is the strong amplitude of the flow perturbation, causing a periodic reversal in the directi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…The strongest and cleanest signal in the internal reflectors is that of the semidiurnal M 2 constituent. For FRIS, ice shelf tilt has been shown to explain semidiurnal tidal variations in ice shelf flow (Makinson et al, 2012;Rosier & Gudmundsson, 2019). M 2 being the strongest signal in the internal reflectors is therefore consistent with M 2 having the largest amplitude in the ocean tidal model (Figure 2a).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The strongest and cleanest signal in the internal reflectors is that of the semidiurnal M 2 constituent. For FRIS, ice shelf tilt has been shown to explain semidiurnal tidal variations in ice shelf flow (Makinson et al, 2012;Rosier & Gudmundsson, 2019). M 2 being the strongest signal in the internal reflectors is therefore consistent with M 2 having the largest amplitude in the ocean tidal model (Figure 2a).…”
Section: Resultssupporting
confidence: 62%
“…Rosier and Gudmundsson (2018) suggested a flexural softening mechanism that should give rise to these double frequencies at significant levels. However, Rosier and Gudmundsson (2019) concluded that this mechanism may not be important at FRIS.…”
Section: 1029/2019jf005280mentioning
confidence: 99%
“…The grounding‐line position as defined here represents the position downstream of which a significant volume of water is retained between the ice and the bed, lubricating the contact such that the till exerts very little basal drag on the flow of the ice. Rosier and Gudmundsson (2020) highlight the sensitive role that variations in drag in the grounding zone play in setting the velocity response of ice shelves. In this way, modulations of horizontal ice velocity can be understood through the modulation of this position of decreased contact.…”
Section: Resultsmentioning
confidence: 99%
“…While these remotely sensed measurements reveal large-scale trends in ice sheet variability, their coarse temporal resolutions do not capture variations across the broad range of time scales over which ocean processes influence ice sheet change. High temporally resolved, long-term surface-based measurements of ice thickness from phase-sensitive radars (e.g., Vaňková et al, 2020) and ice velocity from global positioning systems (e.g., Rosier & Gudmundsson, 2020) have exposed some of these processes on both grounded and floating ice.…”
Section: Introductionmentioning
confidence: 99%